Pengembangan Sistem Pemesanan Kue Berbasis Website Menggunakan Midtrans Webservice Sebagai Payment Gateway (Studi Kasus: Toko Kue De Tasty) - Muhammad Arief Habibirrahman; Widhy Hayuhardika Nugraha Putra; Buce Trias Hanggara (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2022)
De Tasty is one of the cake shops in Boyolali City that provides various kinds of cake products. In addition, this cake shop also opens a cake ordering service according to customer wishes. But until now cake orders are still done by visiting a cake shop or ordering directly using a cellphone via social media. Ordering cakes through social media is still done conventionally, where customers send photos of payments and store employees will record the transaction data. Ineffective payment and cake ordering mechanisms can cause invalid transaction data, because checking and recording data is done manually. In this study, a cake ordering system that is integrated with the Midtrans payment gateway will be developed to make it easier for store employees to manage orders and record transaction results. In addition, it will also make it easier for customers to pay for orders without having to send photos of proof of payment to store employees. In this research, a cake ordering system will be developed using the Laravel framework and integrated with the Midtrans payment gateway using the concept of Service Oriented Architecture. The test method used is usability testing using the System Usability Scale which obtained a final score of 74.13 which means the cake ordering system on the Acceptability Ranges assessment obtained an acceptable status based on a questionnaire survey of 20 respondents.